Physicochemical, techno-functional, and proteolytic effects of various hydrocolloids as fat replacers in low-fat cheddar cheese - Murtaza, Mian Shamas; Sameen, Aysha; Rehman, Abdur; Huma, Nuzhat; Hussain, Fatma; Hussain, Shahzad; Cacciotti, Ilaria; Korma, Sameh A.; Ibrahim, Salam A.; Ma, Yong Kun (Frontiers in Sustainable Food Systems, 2024)
This study aimed to investigate the physiochemical properties, techno-functional at-tributes, and proteolytic impacts of incorporating different hydrocolloids as fat substitutes in low-fat cheddar cheese. The effects of hydrocolloids (gums) and dietary fiber, both individ-ually and in combination, were studied for the production of low-fat cheddar cheese with the same textural and functional attributes as full-fat cheese. Physicochemical, techno-functional attributes, organic acid, and proteolysis analyses were performed at 0 and 90-day storage intervals. The results of different combinations were compared with positive (4% fat) and negative (2% fat) controls, and it was observed that using fat replacers improved the textural and functional properties of low-fat cheddar cheese. A significant difference was observed in the meltability and flowability of low-fat cheese samples with different analytes. The prote-olysis pattern in low-fat cheese also differed from that of its full-fat counterpart. Three treatments were considered the best: T2 (guar gum at 0.45%), T6 (guar gum, inulin, and re-sistant starch at 33%), and T7 (all analytes at equal concentrations). The findings revealed that hydrocolloids notably improved the texture, meltability, and sensory characteristics of low-fat cheddar cheese. Additionally, SEM images revealed that the microstructure variations can be attributed to changes in the hydrocolloids water retention and fat content. The Pearson correlation coefficient revealed relationships between different functional properties, con-tributing to understanding how hydrocolloids as fat replacers impact the overall quality of low-fat cheddar cheese. This study offers useful information for the dairy sector to manu-facture low-fat cheeses that have enhanced customer acceptance and provide nutritional ad-vantages.